Soil aggregates impact nitrifying microorganisms in a vertisol under diverse fertilization regimes. (2nd October 2019) - Han, Shun; Luo, Xuesong; Tan, Shuang; Wang, Jianfei; Chen, Wenli; Huang, Qiaoyun
Abstract: Ammonia oxidizers (ammonia‐oxidizing archaea (AOA) and bacteria (AOB)), nitrite oxidizers (e.g., Nitrobacter and Nitrospira ) and comammox Nitrospira play important roles in the nitrogen cycle in agroecosystems, yet their activities and abundance in soil microhabitats under environmental disturbances remain unclear. In this study, we collected samples from treatment plots in a field experiment established in 2010 in a lime concretion black soil in central China to investigate the effects of varying inorganic and organic fertilizer managements in a wheat–maize crop rotation, in order to investigate the impacts on the abundance and activities of ammonia and nitrite oxidizers inhabiting different microenvironments in soil, represented by three soil aggregate size fractions. The treatments were: control without fertilizer (CK), chemical fertilization (NPK), NPK and straw (NPKS), NPKS and pig manure (NPKSP) or cow manure (NPKSC). The potential nitrite oxidation activity (PNO) and soil nutrients (soil carbon, nitrogen and phosphorus content) were the highest in the microaggregates, followed by those in the macroaggregates and silt+clay fractions in all the plots. Both the ammonia and nitrite oxidizers were more abundant in the macroaggregates and microaggregates than in the silt+clay fractions. A two‐way analysis of variance (ANOVA) indicated that the soil aggregate size had a significant influence on the abundance of ammonia and nitrite oxidizers and the soil nutrients. We also found a significant positive correlation between PNO and the nitrite oxidizer and AOA abundance. In addition, the abundances of the ammonia oxidizers (AOA and AOB) and nitrite oxidizers ( Nitrobacter and Nitrospira ) were positively correlated with each other. Overall, the soil aggregates with a higher inorganic nutrient and organic carbon content may provide a better protective microenvironment to guard against environmental disturbances and facilitate the inhabitation of ammonia and nitrite oxidizers, which cooperate in the nitrogen cycling process. Highlights: Nitrifying guilds and their activities were investigated under soil aggregates in a Vertisol. Soil aggregates of different sizes provide spatially heterogeneous habitats for nitrifying guilds. Ammonia‐ and nitrite‐oxidizer abundances and their activities are controlled by soil aggregate size. Soil aggregates with higher nutrients may provide a better protective habitat for nitrifying guilds.